• Status: Solved
  • Priority: Medium
  • Security: Public
  • Views: 476
  • Last Modified:

Reverse trajectory calculation

Using the following rules:

x = vx * t
y = vy * t + c * t
sqr( vx * vx + vy * vy ) = 1

When the numbers c, x and y are known,
how do I calculate t, vx and vy for the lowest positive value of t?
how do I calculate vx and vy for a given value of t?
0
JasonMewes
Asked:
JasonMewes
  • 6
  • 3
  • 2
  • +1
1 Solution
 
leizCommented:
Since c, x, and y are known, for a given t:

from (1), we can have: vx = x/t
from (3), we can have vy = sqrt(1- vx*vx) = sqrt(1- (x/ t) * (x/t))

considering (2), after a series of transformation:
t=sqrt(x^2 + (y-ct)^2) or t = -sqrt(x^2 + (y-ct)^2)

It is can be inferred that the lowest positive value of t is location, (x,y), dependent. With x = 0, y = ct, t can be 0.
0
 
aburrCommented:
Alternatively (and a bit simpler) you have
vy = y/t - c
0
 
leizCommented:
the bottom line for this problem is:

although it is routine to calculate the trajectory based on known initial condition, the answer to the reverse problem may not always be unique or finite.
0
Cloud Class® Course: Ruby Fundamentals

This course will introduce you to Ruby, as well as teach you about classes, methods, variables, data structures, loops, enumerable methods, and finishing touches.

 
aburrCommented:
I beleive there is some difficulty with the equationb
t=sqrt(x^2 + (y-ct)^2) or t = -sqrt(x^2 + (y-ct)^2)
The units do not check out.
0
 
ozoCommented:
x = vx * t
y = vy * t + c * t
sqr( vx * vx + vy * vy ) = 1
y = (vy+c) * t
vx = x/t
vy = y/(t+c)

0
 
aburrCommented:
oxo
are you sure your vy is correct? It looks to me that it has units trouble.
0
 
ozoCommented:
No more units trouble than the original rules
What are the units of y, vy, c and t?
0
 
aburrCommented:
If you know x, y, and c there is only one value of t which will fit.
(actually possibly two because there is a square root involved)
0
 
aburrCommented:
L      L/T      L/T      and    T


your last equation returns to y = vy *t + vy*c
0
 
ozoCommented:
sorry, you're right
vy = y/t - c
0
 
aburrCommented:
t = -2c*y +- (sqr (4 c^2*t^2 + 4 (V^2-c^2)*(x^2+y^2))/(2(V^2-c^2)))


Where V is the 1 in your velocity equation.


0
 
JasonMewesAuthor Commented:
leiz, your solution works quite well for the problem I describes - so I will award you your points.
however, i made I mistake in the formulation, so I'm going to add another question with the correct formulas.
0
Question has a verified solution.

Are you are experiencing a similar issue? Get a personalized answer when you ask a related question.

Have a better answer? Share it in a comment.

Join & Write a Comment

Featured Post

Cloud Class® Course: Microsoft Exchange Server

The MCTS: Microsoft Exchange Server 2010 certification validates your skills in supporting the maintenance and administration of the Exchange servers in an enterprise environment. Learn everything you need to know with this course.

  • 6
  • 3
  • 2
  • +1
Tackle projects and never again get stuck behind a technical roadblock.
Join Now